First species of Tinaroo Chandler from outside Australia (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2016)
As a result of Chandler’s recent generic revision of the Australian Pselaphinae (Chandler 2001), eleven genera of the tribe Batrisini are currently known to occur in Australia. Seven of them (Amblybatrisus Chandler, Daintree Chandler, Gadgarra Chandler, Mossman Chandler, Neurum Chandler, Spurgeon Chandler, and Tinaroo Chandler) are so far endemic, and four genera (Ancistromus Jeannel, Batrisocenus Raffray, Coryphomodes Jeannel, and Hypochraeus Raffray) also occur in the Oriental region.